Corrosion potential of reinforced steel in reinforced concrete in Kabupaten Bireun: Analysis of groundwater content used as a concrete mixture. (August 2019) - Kurnia, R D I; Suhaimi,; Huzni, S; Fonna, S
Abstract: The use of groundwater as a mixture in making reinforced concrete is common in Bireun District, Aceh. This research is the initial stage of investigating the relationship between the quality of concrete and water resistance as a mixture in Bireun Regency. At this stage, the research focus is directed to find out what elements are contained in groundwater in five locations in Kabupaten Bireun, namely Gampong Paya, Gampong Teupok Teungoh, Gampong Pulo Lawang, Gampong Lhok Awe Baroh and Gampong Lhok Awe. Water content testing is carried out by referring to SNI 06-6989.14-2004 and SNI 06.6989.19: 2009. The results analyzed and compared with the reference of ASTM C 1602 M-04 standard. Laboratory test results show that chloride, sodium, sulfate and dissolved oxygen differ from location to location. Chloride content in two locations, Gampong Paya and Tumpok Teungoh, is far above the standard content set in the ASTM C 1602 M-04 standard. While at three other locations, chloride content was below the limit of ASTM C 1602 M-04. Investigation of the potential for corrosion of reinforcing steel in reinforced concrete using groundwater as a mixture in five locations will provide further information.